Odpowiedzi

2010-03-04T17:34:13+01:00
A.
-4
-4
-11
13
2
-17

b.
-4
-20
-71
15
-9
-15

c.
-6
10
20
-3
-76
-38
1 5 1
2010-03-04T17:38:08+01:00
A
=-4
=-4
=-11
=13
=2
=-17
B
=-4
=-20
=-71
=15
=-9
=-15
C
=-6
=10
=20
=-3
=-76
=-38
2010-03-04T17:40:32+01:00
A) 2 + (-6) = -4
-21 + 17 = -4
-3 + (-8) = -11
7 + (-6) + 12 = 13
15 + (-2) + (-11) = 2
-8 + (-6) + (-3) = -17

b) 8 - 12 = -4
-14-6 = -20
-24-47 = -71
7 - ( -8) = 15
-15 - (-6) = -9
-23 - (-8) = -15

c) 6 + (-8) -4 = -6
15 + (-7) - (-2) = 10
5 - 12 - (-27) = 20
-5 - ( -13) + (-11) = -3
-12-23-41 = -76
-14 - 6 + (-18) = -38